Equity of expenditure changes associated with a sweetened-beverage tax in Tonga: repeated cross-sectional household surveys - Andrea Teng; Bertrand Buffière; Murat Genç; Telekaki Latavao; Viliami Puloka; Louise Signal; Nick Wilson (BMC, 2021)
Abstract Background The aim of this study was to examine changes in beverage expenditure patterns before and after a T$0.50/L sweetened-beverage (SB) excise was introduced in Tonga in 2013, by household income, household age composition and island of residence. Methods Two cross-sectional surveys involved households being randomly sampled (the Household Income and Expenditure Surveys in 2009 (n = 1982) and 2015/16 (n = 1800)). Changes in soft drink (taxed), bottled water, and milk (both untaxed) expenditure were examined namely: (i) prevalence of households purchasing the beverage; (ii) average expenditure per person (inflation-adjusted); (iii) expenditure as a proportion of household food budget; and (iv) expenditure per person as a proportion of equivalised income. Results The pattern found was of decreases in all soft drink expenditure outcomes and these appeared to be greater in low-income than high-income households for purchasing prevalence (− 30% and − 25% respectively, t-test p = 0.98), per-capita expenditure (− 37% and − 34%, p = 0.20) and food budget share (− 27% and − 7%, p = 0.65), but not income share (− 6% and − 32%, p = 0.71). The large expenditure increases in bottled water appeared to be greater in low-income than high-income households for purchasing prevalence (355 and 172%, p = 0.32) and food budget share (665 and 468%, p = 0.09), but greater in high-income households for per-capita expenditure (121 and 373%, p < 0.01) and income share (83 and 397%, p = 0.50). Conclusions The sweetened-beverage tax was associated with reduced soft drink purchasing and increased bottled water expenditure. Low-income households appeared to have slightly greater declines in soft drink expenditure.